Umbilical Cord Pericytes Provide a Viable Alternative to Mesenchymal Stem Cells for Neonatal Vascular Engineering - Cathery, William; Faulkner, Ashton; Jover, Eva; Rodriguez-Arabaolaza, Iker; Thomas, Anita C.; Avolio, Elisa; Caputo, Massimo; Madeddu, Paolo (Frontiers in Cardiovascular Medicine, 2021)
Reconstructive surgery of congenital heart disease (CHD) remains inadequate due to the inability of prosthetic grafts to match the somatic growth of pediatric patients. Functionalization of grafts with mesenchymal stem cells (MSCs) may provide a solution. However, MSCs represent a heterogeneous population characterized by wide diversity across different tissue sources. Here we investigated the suitability of umbilical cord pericytes (UCPs) in neonatal vascular engineering. Explant outgrowth followed by immunomagnetic sorting was used to isolate neural/glial antigen 2 (NG2)+/CD31- UCPs. Expanded NG2 UCPs showed consistent antigenic phenotype, including expression of mesenchymal and stemness markers, and high proliferation rate. They could be induced to a vascular smooth muscle cell-like phenotype after exposure to differentiation medium, as evidenced by the expression of transgelin and smooth muscle myosin heavy chain. Analysis of cell monolayers and conditioned medium revealed production of extracellular matrix proteins and the secretion of major angiocrine factors, which conferred UCPs with ability to promote endothelial cell migration and tube formation. Decellularized swine-derived grafts were functionalized using UCPs and cultured under static and dynamic flow conditions. UCPs were observed to integrate into the outer layer of the graft and modify the extracellular environment, resulting in improved elasticity and rupture strain in comparison with acellular grafts. These findings demonstrate that a homogeneous pericyte-like population can be efficiently isolated and expanded from human cords and integrated in acellular grafts currently used for repair of CHD. Functional assays suggest that NG2 UCPs may represent a viable option for neonatal tissue engineering applications.